Morality for beautiful girls eaudiobook - McCall Smith, Alexander (The No. 1 Ladies' Detective Agency, 2003)
The quick-witted, good-natured detective Mma "Precious" Ramotswe shines in this irresistible bestseller. Between intriguing new cases and troubling personal developments, Precious' hands are full. The four Miss Beauty and Integrity pageant finalists may have questionable moral fiber, and the brother of an important government worker has allegedly been poisoned. On top of all that, Precious' reliable fiancE might be hiding something.